2012
DOI: 10.5402/2012/765476
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Female Iron-Deficiency Anaemia in India: Is Vegetarianism the Major Obstacle?

Abstract: Objectives. We examined the influence of vegetarian diet on the risk of developing anaemia among Indian women and suggest initiatives for addressing diet-related iron-deficiency anaemia. Methods. We analysed data on diet, social class, and haemoglobin levels from the nationally representative Indian National Family and Health Survey 2005/06 for a sample of 81,301 women aged 15-49 years using logistic regression models. Results. After controlling for individual-level factors and household level socioeconomic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 30 publications
(31 reference statements)
4
38
0
1
Order By: Relevance
“…However, a significant association was observed in a study by Cheema et al, where vegetarians were found to be predominantly affected. Similar results were observed by Rammohan et al and Singh et al 19,20 Most of the patients who were anemic were multiparous, with more than 3 gravida. This was in concurrence with a study in Nigeria, by Zama et al, who found that more of multiparous women were anemic.…”
Section: Discussionsupporting
confidence: 88%
“…However, a significant association was observed in a study by Cheema et al, where vegetarians were found to be predominantly affected. Similar results were observed by Rammohan et al and Singh et al 19,20 Most of the patients who were anemic were multiparous, with more than 3 gravida. This was in concurrence with a study in Nigeria, by Zama et al, who found that more of multiparous women were anemic.…”
Section: Discussionsupporting
confidence: 88%
“…13 Recent estimates of iron-deficiency anaemia show that 52% of Indian women aged 15-49 years are anemic. 18 Similarly in present study maximum females showed microcytic anemia which has its most common cause to be iron deficiency. The population group with the greatest number of individuals affected is pregnant women (41.8%).…”
Section: Discussionmentioning
confidence: 82%
“…18 But according to our study platelet count was found to be reducing with reduction in hemoglobin count.…”
Section: Discussionmentioning
confidence: 99%
“…Present study are similar to, a cross sectional study in New Delhi had revealed that there was a trend of decreasing severity of anemia with higher per capita income as found in the present study. 15 In India, pregnant Hindu women are advised to avoid non vegetarian diet during pregnancy as it generates heat. Dietary pattern significantly influences anemia status.…”
Section: Discussionmentioning
confidence: 99%